PENINGKATAN AKTIVITAS BELAJAR SISWA DALAM MATA PELAJARAN BAHASA INGGRIS MELALUI MODEL PEMBELAJARAN SILENT WAY DI KELAS X SMKN 1 TALAMAU - muhammad naim (STKIP Pesisir Selatan, 2017)
ABSTRACTBased on the learning activities of students of Class X SMKN 1 Talamau in English subjects found that the learning activities of students in English is still very low. The purpose of this study is to describe and obtain information about the Enhancement of Student Learning Activities in English Subjects through the model of Silent Way learning in Class X SMKN 1 Talamau West Sumatra Province. This study is a classroom action research. The research procedures in this study include planning, action, obeservation and reflection. This study consists of two cycles with four meetings. Research subjects consist of 12 students of Class X SMKN 1 Talamau. The research data was collected by using observation sheet. Data were analyzed using percentages. Based on the results of research and discussion that has been stated in the previous chapter, it can be concluded that it can be concluded that the model of demonstration demonstration can increase student learning activities in English subjects in SMKN 1 Talamau. Student learning activity in cycle I was 71.72 (enough) increased to 81.56 (good) with an increase of 9.84.Keywords: Learning Activity, English Education, Silent Way learning model